6′-O-Caffeoylarbutin from Que Zui tea ameliorates acetaminophen-induced liver injury via enhancing antioxidant ability and regulating the PI3K signaling pathway. Issue 9 (20th April 2022) - Wang, Yong-Peng; Wang, Yu-Dan; Liu, Ya-Ping; Cao, Jian-Xin; Yang, Mei-Lian; Wang, Yi-Fen; Khan, Afsar; Zhao, Tian-Rui; Cheng, Gui-Guang
Abstract : 6′- O -Caffeoylarbutin from Que Zui tea ameliorates acetaminophen-induced liver injury in vitro and in vivo . Abstract : Que Zui tea (QT), a traditional herbal tea in China, has a significant hepatoprotective effect. 6′- O -Caffeoylarbutin (CA) is the most abundant chemical compound in the QT. However, the hepatoprotective effect of CA has not been investigated. This study is aimed to evaluate the protective effect of CA on acetaminophen (APAP) induced hepatotoxicity in vivo and in vitro and its possible underlying mechanism. In APAP-induced HepG-2 cells, CA inhibited intracellular ROS accumulation and cell apoptosis, and improved the expression of antioxidants including SOD, CAT and GSH. In APAP-administrated mice, CA pretreatment remarkably ameliorated the histopathological damage and inflammatory response, and antioxidant enzyme activity in the serum and liver tissues. Moreover, the immunohistochemistry and immunofluorescence assay results revealed that the CA markedly reduced ROS production and apoptosis, and activated antioxidant transcription factor Nrf2 in the liver. Meanwhile, molecular docking results showed that the strong binding force of CA and PI3K was due to the higher number of hydrogen- and π-bonds with active site residues. Notably, CA pretreatment significantly regulated the expression of PI3K, Akt, Nrf2, NQO1, HO-1, Bcl-2, Bax, caspase-3, and caspase-9 proteins in APAP-treated liver tissues. These data demonstrated that CA had a protective effect against APAP-induced hepatotoxicity via regulating the PI3K/Akt and Nrf2 signaling pathway.